2003
DOI: 10.1046/j.1439-0388.2003.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes for growth traits in beef cattle crosses Bos taurus × Bos indicus

Abstract: Records of 192 Hard henu cattle pertaining to first lactation traits over a period of 6years from 2008 to 2014were collected from history cum pedigree sheets maintained at Cattle breeding farm, Department of Animal Genetics and Breeding Lala Lajpat Rai University of Veterinary and Animal Sciences, Hisar. Data were analysed by LSML(Harvey, 1990) using mixed linear model having effect of sire as random and that of year and season of calving as fixed. The first lactation traits studied were first lactation milk y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 12 publications
2
47
0
7
Order By: Relevance
“…These authors observed a negative effect of substitution of allele A with allele B of the κ-casein polymorphism on EPD (Expected Progeny Difference) for birth weight, weaning weight and maternal milk production, indicating that the A allele is favorable to these traits. However, our results agree with those obtained by Regitano et al (1999) and Tambasco et al (2003), who did not observe any influence of this polymorphism on growth traits in Canchim beef cattle and F1 animals of Canchim x Nelore, Simmental x Nelore and Angus x Nelore crosses, respectively. According to Pomp et al (1994), these contradictions can be explained by differences in the linkage equilibrium between markers and quantitative traits loci in the various populations studied, or by different epistatic interactions between the genetic bases of these populations and quantitative trait loci.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These authors observed a negative effect of substitution of allele A with allele B of the κ-casein polymorphism on EPD (Expected Progeny Difference) for birth weight, weaning weight and maternal milk production, indicating that the A allele is favorable to these traits. However, our results agree with those obtained by Regitano et al (1999) and Tambasco et al (2003), who did not observe any influence of this polymorphism on growth traits in Canchim beef cattle and F1 animals of Canchim x Nelore, Simmental x Nelore and Angus x Nelore crosses, respectively. According to Pomp et al (1994), these contradictions can be explained by differences in the linkage equilibrium between markers and quantitative traits loci in the various populations studied, or by different epistatic interactions between the genetic bases of these populations and quantitative trait loci.…”
supporting
confidence: 93%
“…Regitano et al (1999) did not observe allele variations between different generations of a Canchim herd and suggested that this polymorphism is not associated with phenotypic traits subjected to selection in this herd. Similarly, Tambasco et al (2003) did not observe an isolated influence of the LGB/HaeIII polymorphism on the growth traits of crossbred Canchim x Nelore, Simmental x Nelore and Angus x Nelore cattle. However, these authors found a significant interaction (epistasis) between this marker and a polymorphism of the growth hormone gene influencing weight gain.…”
mentioning
confidence: 79%
“…Tambasco et al (2003) observed a positive association between genotype LV and daily body weight gain (BWG) from weaning to yearling in Bos taurus X Bos indicus crosses. It is also in agreement with the results observed in a Simmental population, where the LV genotype was associated with a higher BWG than LL and VV (Schlee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the results of observed heterozygosity analysis (H o ) and expected heterozygosity (He) at GH|AluI gene indicated no statistically difference (Table 2). Tambasco et al (2003) stated that if the value of observed heterozygosity (H o ) is much lower compared to that value of expected heterozygosity (H e ), it might indicate a more intense selection or a higher degree of inbreeding.…”
Section: Heterozigositymentioning
confidence: 99%